When the Cough Does Not Improve: A Review on Protracted Bacterial Bronchitis in Children - Gallucci, Marcella; Pedretti, Melissa; Giannetti, Arianna; di Palmo, Emanuela; Bertelli, Luca; Pession, Andrea; Ricci, Giampaolo (Frontiers in Pediatrics, 2020)
Chronic cough is defined as a daily cough that persists longer than 4 weeks. Protracted bacterial bronchitis (PBB) is a common cause of chronic wet cough in preschool children with no symptoms or signs of other specific causes, and resolution usually follows a 2-week course of an appropriate oral antibiotic. The diagnosis is mainly clinical; generally, no instrumental examinations are necessary. The most common bacteria found in the bronchoalveolar lavage (BAL) of subjects with PBB include Haemophilus influenzae, Streptococcus pneumoniae, and Moraxella catarrhalis. Nowadays, there is no certain evidence of the role of viruses in PBB pathogenesis even though different types of viruses have been detected in BAL from children with PBB. Airway malacia is commonly found in children with PBB; conversely, there is no correlation with any type of immunodeficiency. Amoxicillin-clavulanate acid is the most commonly used antibiotic, as first-line, prolonged therapy (longer than 2 weeks) is sometimes required to cough resolution. When the wet cough does not improve despite prolonged antibiotic treatment, an underlying disease should be considered. Moreover, there are several hypotheses of a link between PBB and bronchiectasis, as recent evidences show that recurrent PBB (>3 episodes/years) and the presence of H. influenzae infection in the lower airways seem to be significant risk factors to develop bronchiectasis. This underlines the importance of a close follow-up among children with PBB and the need to consider chest computerized tomography (CT) in patients with risk factors for bronchiectasis. In this brief review, we summarize the main clinical and pathogenetic findings of PBB, a disease that may be related to a relevant morbidity and decreased quality of life during the pediatric age.